An Examination of the Relationship Between Interperiod Tax Allocation and Present-Value Depreciation. - Meyers, Stephen L. (The Accounting Review, 1973)
The article focuses on the source of the conflict between present-value depreciation and interperiod tax allocation techniques for determining balance sheet values in accounting practice. A major portion of the controversy over the appropriate treatment of income taxes in accounting results from disagreement on the nature of income taxes. Even if one accepts the unproven assumption that income taxes are an expense, the question of the relationship between income taxes and asset valuation remains to be answered. Supporters of tax allocation, on the other hand, regard asset valuation and income tax accounting as separate problems. The impact of income taxes during a specific accounting period should be measured by the amount of tax which will be paid on income earned and reported during that period, regardless of when the taxes are paid. The article concludes that the basic benefits associated with present-value depreciation can be realized under existing tax laws and accepted methods of accounting for income taxes if annual depreciation charges are based on pre-tax income streams.